Micro-nutrients in East African lowlands: Are they needed to intensify rice production? - Awio, T.; Senthilkumar, Kalimuthu; Dimkpa, C.; Otim-Nape, G.W.; Kempen, B.; Struik, P.C.; Stomp, T.J. (Elsevier, 2021)
Rice is a staple food and cash crop for smallholder farmers in sub-Saharan Africa; however, yields are very low, with indications that both macro and micro-nutrients may limit rice productivity in East Africa next to the need for good agronomic practices. Diagnostic on-farm experiments were conducted in Uganda and Tanzania between 2015 and 2017 to assess the contribution of macro, secondary and micro-nutrients on lowland rice yield and identify options by which smallholder farmers can increase productivity. All treatments included good agronomic practices combined with: zero fertilisation as a control, NPK fertilisation with and without secondary and micro-nutrients (B, Mn, Zn, Cu, Mg, S), and/or treatments where B, Mn and Zn were omitted one at a time from the NPK + secondary and micro-nutrient treatment. NPK fertilisation significantly (p < 0.05) increased grain yield under irrigated condition by ca. 32 and 29 % during 2015 and 2016, and 24 and 100 % during 2016 and 2017 in Tanzania and Uganda, respectively; however, inconsistent effects were observed under rainfed condition. Observed higher yields corresponded mainly to higher panicle number with an additive effect of grains per panicle indicating major effects were at earlier growth stages supporting higher sink size development. Adding secondary and micro-nutrients to NPK enhanced yield significantly (p < 0.05) under irrigated condition in Tanzania 2015 and 2016 by 7 and 11 %, respectively, while varying results were obtained under rainfed condition. In Uganda, no significant (p> 0.22) effects of secondary and micro-nutrients were observed in both years and growing conditions. This study indicates that the first step to improving lowland rice productivity is proper water management, under otherwise also good crop management in terms of timely transplanting and weeding, and further yield gains can be realised with NPK fertilisation. Secondary and micro-nutrients were effective only when NPK were applied and on the fluvisols of Tanzania, and were not co-limiting yield on the plintosols of Uganda.